L’argumentation journalistique, déclin ou renouveau ? - Nicolas Pélissier (Cahiers de Narratologie)
After defining the argumentative function of journalism, this paper puts in discussion the possible decline of this function nowadays. The text  proposes a diachronic approach to the relations between journalism and argumentation, from the Renaissance to the end of the 20th century. This approach highlights the advent of opinion journalism centered on argumentation in the Age of Enlightenment. It shows also the progressive decline of this model in favor of a facts-centeredjournalism considering the news as a data to process and a commodity to sell and value. In a second step, a more synchronic approach shows how ICT's tend to enable journalistic argumentation. at the same time digital media promote a more factual, even “artificial” journalism, but also more and more emotional, under the influence of dominant styles of communication within the blogs and social media. To conclude, the author finds that the peripheries of journalism seem to adopt a more argumentative and deliberative model, while the "hard core" of the media system remains far away from this model.  We can observe the growth of “argumentative prostheses” of contemporary journalism, revealing a post-modernity that focuses on the expressive and functional dimension of journalisme ... a bit far away from its democratic dimension.